Prospective analysis of the association of infection with CagA bearing strains of Helicobacter pylori and coronary heart disease. Issue 1 (1st July 2002) - Singh, R K; McMahon, A D; Patel, H; Packard, C J; Rathbone, B J; Samani, N J
Abstract : Objective: To see whether it was possible to replicate in a prospective study the association recently reported between infection with the more virulent (type 1) cytotoxin associated gene A (CagA) antigen carrying strains of Helicobacter pylori and increased risk of coronary heart disease. Design and setting: Nested case–control study in a clinical outcomes trial. Subjects: Participants in the West of Scotland coronary prevention study. Methods: H pylori CagA serological status was determined in plasma samples of 201 subjects (cases) who subsequently had a coronary event during follow up and in 414 subjects (controls) matched for age and smoking who remained event-free, using a semiquantitative commercial enzyme linked immunosorbent assay (ELISA) kit against the p120 antigen of CagA. Results: 105 (52%) in the case group and 176 (43%) in the control group were seropositive (odds ratio (OR) 1.49, 95% confidence interval (CI) 1.06 to 2.10, p = 0.022). The association remained significant after adjustment for blood pressure, body mass index, plasma concentrations of low density lipoprotein and high density lipoprotein cholesterol, history of hypertension and diabetes, statin treatment, and socioeconomic status (OR 1.51, 95% CI 1.06 to 2.16, p = 0.023). Baseline inflammatory markers (white cell count, C reactive protein, fibrinogen) were not significantly increased in either H pylori CagA positive cases or controls. Conclusions: The findings provide support from a prospective study for the hypothesis that there is an association between infection with CagA bearing strains of H pylori and coronary heart disease. The mechanism(s) underlying the association remain to be elucidated.